PENGGUNAAN DAN KEBIJAKAN MEDIA SOSIAL - Kosasi, Rindi; Nurmandi, Achmad; Misran , Misran (Universitas Negeri Surabaya, 2024)
This research aims to study regulations on the use of social media around the world. This study uses a qualitative scientometric approach. The data source for this study was taken from the Scopus Database with the keywords